Research productivity and values - Callaghan, CW (My University, 2014)
According to the predictions of convergence theory, the implementation of best practices derived from the global context has been found to be associated with increased performance for both individuals and organisations. However, the values systems of individuals and within organisations have been found to constrain the adoption of best practices. This research tested Schwartz’s basic human values theory and the specific influence of basic human values upon individual work performance in the form of research productivity. The self-enhancement dimension of hedonism was found to be negatively associated with Thompson Reuters (Institute for Scientific Information) and ProQuest International Bibliography of the Social Sciences accredited journal article publication; Department of Education accredited journal article publication; conference proceedings publication; conference presentations and book chapter publication. Worryingly, openness to change values were not found to be associated with higher levels of research productivity. These results are taken to support Kuhn’s theory of paradigmatic values constraints to knowledge creation and scepticism as to the extent to which scientific research productivity is indeed inherently objective or innovative in nature. Recommendations for research practitioners and for further research are offered.
Keywords: Schwartz values theory; Academic publishing; Research outputs